From Pyrenees to Andes: The relationship between transhumant livestock and vultures - Arrondo, Eneko (2023)
Transhumance is the traditional livestock practice consisting in the seasonal movement of herds between winter and summer pastures. Transhumance have important effects on the ecosystem functions from local to regional scales. Here, we 1) explored the relationship of vultures to transhumant herds, and 2) tested whether there is a shift on the use of space by vultures due to the decline of transhumance. For that, we first assessed whether vultures follow transhumant herds in two mountain areas with transhumant tradition, Pyrenees (Spain) and Andes (Argentina). Second, we compared both systems to determine whether the impact of transhumance on the use of space of vultures is greater in the area where transhumance is still relevant (Andes) than where this activity is in decline (Pyrenees). For this purpose, we analyzed the use of the summer pastures made by 50 griffon vultures (Gyps fulvus) and 18 Andean condors (Vultur gryphus), as assessed by GPS tracking. Our findings showed that both species respond to transhumance by making greater use of summer pastures when herds are present. A higher proportion of condors made use of summer pastures than griffons, and condors individually made a more intense use of it than griffons. Differences could be explained by the fact that transhumance in the Andes is still important while in the Pyrenees is declining and the amount of carrion provided is lower. Given that the abandonment of traditional activities is a phenomenon underway, it is urgent to evaluate the effects it will have on biodiversity conservation.